Deprescribing and Optimal Selection of Proton Pump Inhibitors (Contributions of the 26th United Russian Gastroenterology Week) - V. T. Ivashkin; I. V. Maev; A. S. Trukhmanov; A. A. Sheptulin; V. I. Simanenkov; T. L. Lapina; I. B. Khlynov; N. N. Dekhnich; O. D. Lopina; O. P. Alekseeva; N. V. Korochanskaya; M. F. Osipenko; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Presentation of the Forum “Deprescribing and optimal selection of proton pump inhibitors” held in Moscow on 29 September 2020 during the 26th United Russian Gastroenterology Week.Key points. The Forum was aimed at discussing issues associated with improving the proton pump inhibitor (PPIs) therapy in treatment and prevention of acid-related diseases and upper gastrointestinal tract (GIT) disorders induced by non-steroidal anti-inﬂammatory drugs (NSAIDs) and antiplatelet medications. Deprescribing is considered to be an eﬀective strategy of a motivated reduction of the PPI dosage, duration of therapy and the patient’s transfer from a regular to on-demand intake regimen. The choice of PPI may condition an optimal therapy for acid-related diseases.Conclusion. PPIs prevail in therapies for acid-related diseases and NSAID-induced upper GIT lesions. PPI deprescribing should be a strategy of choice if medically indicated. A non-enzymatic metabolism, high acid suppression, stable antisecretory eﬀect from day 1 of therapy and cytoprotective action justify the application of rabeprazole (Pariet®) for optimising therapies for acid-related diseases and implementing the deprescribing strategy.